A review on the tensile properties of bamboo fiber treatments - Muniandy, Moviyndiran; Mustapa, Mohammad Sukri; Ali, Nurdin; Siswanto, Waluyo Adi; Rashid, Azrin Hani Abdul; Masirin, Mohd Idrus Mohd; Wahab, Norfariza Ab; Yaakob, Mohd Yuhazri; Mansor, Mohamad Norani; Wagiman, Abdullah (2023)
Natural fibers, like as bamboo, are easily destroyed by microbes (Biodegradability) and may become an alternative fiber in the future because to their very low supply. Bamboo grows all year and is not impacted by the seasons.Bamboo fiber is a solution to environmental issues, and synthetic fibers business prospects are likely to dwindle as oil prices rise. Bamboo fibre has hydrophilic qualities in its composition, allowing it to absorb more water. The mechanical and physical properties of the resultant composites suffer as a result. This study’s goal is to understand the types and process of each bamboo fibre treatment method, to be able to choose the best treatment method that brings the best tensile strength and to explain why the chosen treatment method yields high tensile strength. The bamboo fibre is extracted using a variety of methods, including mechanical extraction, chemical extraction, and combination (Chemical + Mechanical) extraction.In comparison to other fibre treatments, alkaline treated bamboo fibre with compressed moulding technique(CMT) as the mechanical separation produces a greater tensile strength value(1000 MPa).